Tuning of band gap, spin reorientation transition along with unusual coercivity in CeCr1-xFexO3 (0.2 ≤ x ≤0.5) perovskite nanoparticles - Yadav M.; Kumar L.S.; Pandey G.C.; Rath C. (My University, 2025)
Here, we have investigated structural, optical and magnetic properties of CeCr1-xFexO3 (0.2 ≤ x ≤ 0.5) nanoparticles synthesized through combustion technique. Structural parameters determined from refinement shows that with increase in x from 0.2 to 0.5, both lattice parameters and volume increase. In addition to Fe3+ and Cr3+, we observe Fe2+ and Cr6+ from XPS (X-ray photoelectron spectroscopy) spectra and the concentration of Fe2+ increases more than that of Cr6+, showing an increase in lattice parameters. Band gap varies from 2.56 to 1.15 eV with increasing x from 0.2 to 0.5 which is ascribed to an increase in the ratio of Fe2+ to Fe3+ along with the increase in particle size. Surprisingly, the spin reorientation temperature, TSR increases from 62 K to 138 K with increase in x from 0.2 to 0.5 respectively. The increase in TSR is attributed to the enhanced Ce3+-Fe3+ interaction at the expense of Ce3+-Cr3+ interaction. Besides, an anomalous increase in HC has been observed at the vicinity of TSR irrespective of composition. With increasing x, the increase in Fe2+ concentration introduces double exchange interaction (Cr3+/Fe3+-Fe2+) and results in transition from complex antiferromagnetic (AFM) behavior to ferromagnetic (FM) one when x = 0.5. The enhancement in TSR along with tunable coercivity make these materials a potential candidate for spintronics, and magnetic switching devices. © 2025 Elsevier B.V.